Design and Implementation of Waste Reduction Intelligent Cafeteria System Based on Raspberry Pi. Issue 4 (January 2021) - Zhang, Shuai; Wu, Qiwen; Zhu, Tianyin; Hou, Keyu
Abstract: With the development of higher education in China, the number of college students on campus is increasing, and the number of people eating in college cafeterias also increases. On the one hand, the problem of crowded lines in school cafeterias during peak dining periods is becoming more and more serious, and students have a poor dining experience. On the other hand, it is often difficult to establish an effective communication mechanism between students and cafeterias. The traditional canteen model is difficult to meet the current needs, and the upgrade of the canteen system in universities is urgent. This paper designs a set of waste reduction intelligent cafeteria system based on Raspberry Pi to reduce waste. The whole system effectively solves the problems of traditional canteens, and establishes a certain reward mechanism to encourage students to use up the purchased dishes and reduce waste. The university canteen provides a practical model for improving service quality and reform and transformation.